1998
DOI: 10.1128/aem.64.4.1379-1384.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Adhesion of Vibrio Strain AK-1 to Oculina patagonica and on Coral Bleaching

Abstract: Laboratory aquarium experiments demonstrated thatVibrio strain AK-1 caused rapid and extensive bleaching of the coral Oculina patagonica at 29°C, slower and less-complete bleaching at 23°C, and no bleaching at 16°C. At 29°C, the application of approximately 100 Vibrio strain AK-1 cells directly onto the coral caused 50 and 83% bleaching after 10 and 20 days, respectively. At 16°C, there was no bleaching, even with an initial inoculum of 1.2 × 108 bacteria. To begin to understand the effect of seawater temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 39 publications
3
48
0
2
Order By: Relevance
“…Previous studies have demonstrated that V. shiloi adheres to its coral host, O. patagonica, via a L-D-galactoside-containing receptor on the coral surface [10]. The data presented here demonstrate that the receptor is present in the coral mucus and that actively photosynthesizing zooxanthellae inside the coral are required for the receptor to be present in the mucus.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies have demonstrated that V. shiloi adheres to its coral host, O. patagonica, via a L-D-galactoside-containing receptor on the coral surface [10]. The data presented here demonstrate that the receptor is present in the coral mucus and that actively photosynthesizing zooxanthellae inside the coral are required for the receptor to be present in the mucus.…”
Section: Discussionsupporting
confidence: 59%
“…We have demonstrated that the causative agent of bleaching of O. patagonica is a new species of Vibrio, Vibrio shiloi [7^9]. The infectious process requires at least ¢ve distinct and sequential steps: (i) Adhesion of the bacte-rium to the coral surface [10], (ii) penetration into the coral epidermal layer [11], (iii) di¡erentiation into a viable but not culturable (VBNC) state [12], (iv) intracellular multiplication, reaching over 10 8 bacteria per cm 3 coral tissue [11,12] and (v) production of extracellular toxins that inhibit photosynthesis, bleach and lyse zooxanthellae [13,14]. The adhesion, intracellular multiplication and toxin production steps are all temperature dependent, i.e., the necessary virulence factors are produced only when the bacteria are at high (summer) temperatures [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, elevated temperature and bacterial or fungal infection are not mutually exclusive. Many pathogens have the capacity to cause disease only in a host under stressful conditions: increased seawater temperature (or other environmental stress) can trigger mortality by inducing a microbe to be more virulent or the host more vulnerable Toren et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Coral disease hotspots can arise through a number of mechanisms driven by thermal stress. Firstly, elevated SSTs may increase the growth rate and virulence of pathogens, leading to higher pathogen densities and higher rates of infectivity , Toren et al 1998, Harvell et al 2002, Rosenberg et al 2007. Secondly, elevated SSTs may compromise coral immunity resulting in an increased number of susceptible and infected hosts (Ritchie 2006, Lesser et al 2007, Muller et al 2008, Mydlarz et al 2010, Reed et al 2010.…”
Section: Introductionmentioning
confidence: 99%